Porous Calcium Carbonate-Poly-2-Acrylamido-2-Methylpropanesulfonic Acid Microspheres Embedded with Silver-Based Nanoparticles as Potential Antibacterial Carriers for Bone Infections - Rini, Novi Dwi Widya; Asmoro, Adinda; Rachmawati, Systi Adi; Ardy, Husaini; Aimon, Akfiny Hasdi; Kishimura, Akihiro; Katayama, Yoshiki; wibowo, arie (UI Scholars Hub, 2025)
Implant-associated infections (IAIs) are a significant complication following orthopedic surgeries and are mainly caused by Staphylococcus aureus. In this study, microspheres based on hybrid calcium carbonate–poly-2-acrylamido-2-methylpropane sulfonic acid (CaCO3-PAMPS) embedded with silver-based nanoparticles (AgNPs) were developed as potential antibacterial drug carriers for IAIs. AgNPs were prepared via a green synthesis approach, which employed Indonesian wild honey as a reducing and capping agent. PAMPS concentrations (0.025%, 0.050%, and 0.075% w/v) and silver ion (Ag+) concentrations in solution (0%, 2.5%, and 4% w/v) were varied. Scanning electron microscopy images showed that samples with 0.050% w/v PAMPS and 2.5% w/v Ag+ exhibited remarkable stability against recrystallization and aggregation. The sample exhibited more homogeneous, free-standing vaterite particles. Moreover, the particles obtained displayed a porous structure, promising for loading active ingredients. In addition, the X-ray diffraction results confirmed that the Ag-based particles embedded were not only AgNPs but were also predominantly composed of AgCl. AgNPs and AgCl in this sample demonstrated antibacterial activity against Staphylococcus aureus (zone of inhibition of 7.2 ± 0.6 mm). The development of stable, homogeneous microspheres with antibacterial properties and drug-loading potential offers a promising solution for the prevention and treatment of IAIs, addressing a critical challenge in orthopedic surgery.